PENERAPAN TOTAL PRODUCTIVE MAINTENANCE (TPM) PEMBANGKIT LISTRIK WASTE HEAT RECOVERY POWER GENERATION (WHRPG) - Mujayyin, Farid - (Nozzle : Journal Mechanical Engineering, 2022)
Waste Heat Recovery Power Generation (WHRPG) technology is a produces electrical energy technology that from the flue gas from the operation of a cement factory that releases CO2 and converts it into electrical energy in the cement industry. Utilization of the generated electricity can be used as a supply of factory electricity needs such as lighting, equipment and various other facilities. Since 2014-2017 until now, the operation of the WHRPG in the Tuban plant after several times setting hot gas on the conversion system is only able to produce an electricity capacity of 28.6 MW which is still far from the planned capacity target, this requires the right operating strategy to reach a capacity of 30.6 MW of electrical energy. Efforts to increase the production capacity of electricity generation from the utilization of hot flue gas in terms of engine performance readiness aspects of steam power plant technology need to be carried out operational and maintenance planning using application method the inspection, small repair medium repair and overhaul (ISMO). Through total productive maintenance (TPM) technical improvements to WHRPG power plant equipment such as damage to pumps and hot gas settings in boilers and other components, repairs are made to get better performance so that the energy produced can reach 95% at the performance ratio value of capacity predetermined start. It is known and can be improved on the OEE (Overall Effectiveness Equipment) value by implementing total productive maintenance on all power generation equipment so that the combination and maintenance together can increase the production of 30.6 MW of electrical energy can be realized.